Red and Black in Haiti : Radicalism, Conflict, and Political Change, 1934-1957 - Smith, Matthew J., Ph. D. (Book collections on Project MUSE., 2009)
In 1934 the republic of Haiti celebrated its 130th anniversary as an independent nation. In that year, too, another sort of Haitian independence occurred, as the United States ended nearly two decades of occupation. In the first comprehensive political history of postoccupation Haiti, Matthew Smith argues that the period from 1934 until the rise of dictator Francois ""Papa Doc"" Duvalier to the presidency in 1957 constituted modern Haiti's greatest moment of political promise.Smith emphasizes the key role that radical groups, particularly Marxists and black nationalists, played in shap.